Performance analysis of downlink massive MIMO system with precoding techniques and pilot reuse factor - Fikreselam Gared Mengistu; Gebey Admassu Worku (Cogent Engineering, 2023)
AbstractMassive multiple input multiple output (Ma-MIMO) is one of the basic enabler technologies for 5 G wireless communication networks to provide higher spectral efficiency (SE) by using large number of antennas and serves many users simultaneously in the same frequency—time resources. In a time division duplex (TDD) Ma-MIMO downlink (DL) system, the base station (BS) estimates the channel using uplink (UL) training but a pilot contamination (PC) is the major challenge in multi-cell Ma-MIMO system. This challenge causes severe inter-cell interference at the home cell and then limits the performance of the system. Precoding techniques with pilot reuse factor (PRF) are used to mitigate the PC effect. The performance of DL multi cell Ma-MIMO system is analyzed under spatial correleted Rayleigh fading channel with both perfect and imperfect channel state information (CSI). Precoding is used to mitigate the intra-cell interferences and PRF reduces the PC effect by assigning orthogonal pilots to neighboring cells. SE performance of multi cell Ma-MIMO system is analyzed with maximum ratio transmitter (MRT), zero forcing (ZF) and minimum mean square error (MMSE) precoding techniques and combined with PRF. Performance comparison of precoding techniques showed that MMSE provides the best SE performance for both CSI and it has highest SE at PRF of four among all when the number of antennas are changed. When both the number of users (K) and antennas (M) are increased simultaneously and [Formula: see text], the SE is improved by more than 25% and also system performance with perfect CSI is better than imperfect CSI.